Evaluating the efficacy of a novel phytase source - Flohr, J. R.; DeRouchey, Joel M.; Tokach, Michael D.; Dritz, Steven S.; Woodworth, Jason C.; Goodband, Robert D. (My University, 2016)
A total of 350 nursery pigs (PIC 1050 barrows, initially 15.1 kg BW) were used in a 21-d study to determine the available phosphorus (aP) release curve for a novel phytase product (Microtech 5000, VTR Bio-tech Co., Guangdong, China). Pigs were randomly allotted to pens at arrival to facilities and on d 0 of the trial pens were allotted to 1 of 7 treatments in a randomized complete block design. There were 5 pigs per pen and 10 pens per treatment. Pigs were fed corn-soybean meal-based diets formulated to contain 1.25% SID Lys. Experimental treatments consisted of 3 diets formulated to 0.12, 0.18, and 0.24% aP with the only source of added P being an inorganic source (monocalcium P). Then, phytase was added to the diet formulated to 0.12% aP at 4 levels (250, 500, 750, and 1000 FTU/kg). Diets were analyzed for phytase using the AOAC method, and analyzed concentrations were lower than formulated. Diets formulated to contain 250, 500, 750, and 1000 FTU/kg had analyzed concentrations of 155, 335, 465, and 780 FTU/kg, respectively. On d 21, one pig per pen was euthanized and fibulas were collected to determine bone ash weight and percentage bone ash. From d 0 to 21, increasing P from inorganic P or increasing phytase increased ADG (linear, P < 0.01), G:F (linear, P < 0.01 for inorganic P; quadratic, P < 0.03 for phytase), and final BW (linear, P < 0.01). Bone ash weight and percentage were increased (linear, P < 0.01) with increasing inorganic P and increasing phytase. Response criteria, which remained in the linear portion of the quadratic phytase curve (ADG, bone ash weight, and percentage bone ash), were used to calculate aP release curves. When analyzed phytase values and percentage bone ash are used as the predictor variables, aP release percentage for up to 780 FTU/kg of Microtech 5000 phytase can be predicted by the equation (y = 0.000002766761x– 0.000000002225x2– 0.000201841391; r2 = 0.948), where x is the phytase concentration in the diet (FTU/kg).
Citation: Flohr, J. R., DeRouchey, J. M., Tokach, M. D., Dritz, S. S., Woodworth, J. C., & Goodband, R. D. (2016). Evaluating the efficacy of a novel phytase source. Journal of Animal Science, 94, 111-112. doi:10.2527/msasas2016-236
Keywords: Nursery Pig; Phosphorus; Phytase; Agriculture